Three-dimensional analysis of dermal backflow in cancer-related lymphedema using photoacoustic lymphangiography - Anna Oh; Hiroki Kajita; Nobuaki Imanishi; Hisashi Sakuma; Yoshifumi Takatsume; Keisuke Okabe; Sadakazu Aiso; Kazuo Kishi (Archives of Plastic Surgery, 2022)
Background Dermal backflow (DBF), which refers to lymphatic reflux due to lymphatic valve insufficiency, is a diagnostic finding in lymphedema. However, the three-dimensional structure of DBF remains unknown. Photoacoustic lymphangiography (PAL) is a new technique that enables the visualization of the distribution of light-absorbing molecules, such as hemoglobin or indocyanine green (ICG), and can provide three-dimensional images of superficial lymphatic vessels and the venous system. This study reports the use of PAL to visualize DBF structures in the extremities of patients with lymphedema after cancer surgery. Methods Patients with a clinical or lymphographic diagnosis of lymphedema who previously underwent surgery for cancer at one of two participating hospitals were included in this study. PAL was performed using the PAI-05 system. ICG was administered subcutaneously in the affected hand or foot, and ICG fluorescence lymphography was performed using a nearinfrared camera system prior to PAL. Results Between April 2018 and January 2019, 21 patients were enrolled and examined using PAL. The DBF was composed of dense, interconnecting, three-dimensional lymphatic vessels. It was classified into three patterns according to the composition of the lymphatic vessels: a linear structure of lymphatic collectors (pattern 1), a network of lymphatic capillaries and lymphatic collectors in an underlying layer (pattern 2), and lymphatic capillaries and precollectors with no lymphatic collectors (pattern 3). Conclusions PAL showed the structure of DBF more precisely than ICG fluorescence lymphography. The use of PAL to visualize DBF assists in understanding the pathophysiology and assessing the severity of cancer-related lymphedema.